Protective Effect of Apple Cider Vinegar in Hydroxyurea Treated Mice - R.S. Ayoub; T.A. Al-Sandok; S.W. Yousif (College of Education for Pure Sciences, 2005)
Bone marrow depression is the mo:.it serious dose limiting toxicity of hydroxy urea . Natural apple cider vinegar in supposed to have both chemo-proteotive and myelo -stimulatory effects . In this study , hydroxy urea at a dose of 80mg/kg/day orally produced significant depression of red blood cell, adecrease in white blood cells and platelets in mice . 20mg/kg/day of apple cider vinegar seven days after hydroxy urea was administered produced no improvement in red blood cells and white blood cells and platelets counts. The administration of apple cider vinegar with hydroxy urea produced significant (P<0.05) increase in red blood cells and white blood cells while platelets not recovered to normal . The effect of hydroxy urea in mice on protein was observed as depressant effect significantly (P<0,05) on total protein adecrease in albumin and globulin . The administration of apple cider vinegar seven days after hydroxy urea produced no significant effect on globulin and albumin , yet the total protein increased but not significantly . The administration of apple cider vinegar at the same time with hydroxy urea significantly increase total protein and globulin , while no change on albumin level . The results in this study indicate that apple cider vinegar has a protective effect on bone marrow from depressive effect of cyto toxic drug hydroxyurea .